Multi-party efficient audit mechanism for data integrity based on blockchain - Jiashun ZHOU; Na WANG; Xuehui DU (网络与信息安全学报)
A blockchain-based data integrity multi-party high-efficiency audit mechanism (MBE-ADI) for the big data environment was proposed.A hybrid Merkle DAG structure based on data domain was built to organize data, and realized the simultaneous verification of a large number of unstructured data in the big data environment.In order to deal with the problem of large amount of data in the big data environment, a multi copy deterministic verification method based on BLS signature was designed to realize the efficient verification of data integrity supporting multiple copies.A dual verification audit architecture based on consortium blockchain was designed to realize decentralized automatic audit and audit history credible traceability.At the same time, data integrity verification services were provided for data owners and data users to realize reliable acquisition of data.The test proves the feasibility of the system and the efficiency of data integrity audit.